GAMBARAN ASUPAN ZAT GIZI MAKRO DAN STATUS GIZI MAHASISWA POLTEKKES KEMENKES SORONG PADA MASA PANDEMI COVID 19 - Swietienia Daniela Fatie; Anjar Briliannita; Wilma Florensia (Jurusan Keperawatan Poltekkes Kemenkes Sorong, 2021)
The incidence of covid 19 in Sorong City is still high, there are quite a lot of Covid-19 sufferers found in students. Students are agents of change who will change the fate of a nation for the better. This shows how important the role of youth as the nation's next generation. So, they need to get the right nutrients. Macronutrient intake plays an important role in a person's nutritional status because in addition to providing energy for the body and regulating metabolic processes in the body, macronutrients can also accelerate growth and improve tissue systems in the body and improve tissue systems in the body, so that they can function in daily activities. -day, it takes a certain amount of energy or energy. Energy needs can be met by consuming food sources of carbohydrates, protein, and fat. If energy adequacy can be met, the utilization of other nutrients will run optimally. The purpose of this study was to describe the intake of macronutrients (energy, carbohydrates, protein and fat) of students of the DIII Nutrition Study Program at the Health Polytechnic of the Ministry of Health, Sorong during the Covid 19 pandemic. This type of research was descriptive using a cross sectional design. The level of macronutrient intake was assessed using 24-hour Food Recall for 1 week, while the measurement of the nutritional status of respondents was measured based on anthropometric measurements (BMI). The number of respondents is 46 people who meet the inclusion criteria. The results obtained in this study, namely the nutritional status of the highest respondent with good nutritional status (50%), the lowest nutritional status with obesity (8.6%) and poor nutritional status (30.4%). Meanwhile, the average respondent's energy intake is less (86.10%), the respondent's protein intake is on average less (63.4%), the respondent's fat intake is on average less (78.7%) and the respondent's carbohydrate intake is on average. less average (95.6%). During the COVID-19 pandemic from 2020 to 2021, the average student has a good nutritional status. However, the average intake of energy, carbohydrates, protein and fat is still lacking. The nutritional status and availability of food rich in macronutrients for students depends on many factors and further research needs to be done regarding the factors that affect the intake of macronutrients and the nutritional status of students.